High open-circuit voltage roll-to-roll compatible processed organic photovoltaics. Issue 38 (18th September 2020) - Tintori, Francesco; Laventure, Audrey; Koenig, Josh D. B.; Welch, Gregory C.
Abstract : Materials design strategies for high open circuit voltage organic photovoltaics. Abstract : Raising the open circuit voltage ( V oc ) of organic photovoltaic (OPV) devices is one of the key parameters to enhance performance and increase utility. We report an active layer composed of a quinoxaline-based donor polymer and an N-annulated perylene diimide (PDI) dimer which are stable and readily scaled materials and as blended solutions can be processed into films using non-halogenated solvents and slot-die coating methods. OPV devices with a high V oc exceeding 1.2 V were obtained under one sun illumination. Furthermore, the practical application of indoor light recycling is demonstrated, reporting a high device V oc of 1.1 V under LED illumination. Modification of the cathode interlayer or addition of a third component using perylene diimide (PDI) based materials is shown to further enhance device V oc under all operating conditions.